Pengaruh Diabetes Self-Management Education (DSME) Pada Penderita Diabetes Melitus: Literature Review - Setiawan - (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Diabetes Mellitus (DM) is a chronic disease that has complications that can be life-threatening and requires extensive involvement of patients and their families in daily self-care. The Purpose of this study to see the effects of Diabetes Self-Management Education (DSME) in patients with diabetes mellitus. This literature review was conducted from online database such as GoogleScholar, ScienceDirect, ProQuest, Scopus, and Pubmed. The articles was published between 2017-2022 finding 10 relevant journals. The result was the implementation of DSME in patients could been carried out in various timescales.  The more often DSME was given, the better the impact.  DSME could also been given through a variety of media that could been tailored to the needed of people with diabetes.  DSME also provides many benefits for people with diabetes, including increasing knowledge and attitudes about self-care, helping to lowered blood glucose levels, increasing commitment to self-management, reducing anxiety and stressed levels and improving the quality of life for people with diabetes.  Therefore, nurses needed to provided DSME intensively by used effective and efficient learned media for people with diabetes.Keywords: diabetes self-management education; diabetes management;health education